A Combination Method of Costal Cartilage Injection Techniques for Augmentation Rhinoplasty. Issue 8 (26th November 2022) - Gu, Tianyi; Li, Xin; Yang, Xiaoning; Yu, Lu; Ma, Jiguang
Abstract : Background: The multiple toothpick-shaped costal cartilage (MTCC) injection technique was introduced as an improvement based on the free diced costal cartilage (FDCC) injection technique for augmentation rhinoplasty. However, radix irregularities may occur when using the MTCC technique. Considering that the FDCC grafts are easier to shape at the nasal radix, we adopted a combination method of the 2 techniques to achieve natural and smooth contour. Methods: Four patients accepted this method for augmentation rhinoplasty. Through a unilateral marginal incision, the costal cartilage grafts were injected for nasal augmentation at the subperiosteal plane. The FDCC grafts and the MTCC grafts were used for nasal radix and dorsum augmentation, respectively. Nasal contour was adjusted by external shaping. The follow-up ranged from 24 to 43 months. Results: All patients were satisfied with the surgical outcome. There were no major complications occurred during the follow-up. One patient underwent rasping revision due to her own beauty-appreciation changes. Conclusions: The combination method can take advantages of the FDCC and MTCC injection techniques. It can effectively lower the incidence of contour irregularities and graft displacement. Meanwhile, it is easy to perform without special procedure, and is time-saving and cartilage-saving.